Savory memories - Beattie, L. Elisabeth, 1953- (The University Press of Kentucky, 2015)
Writers love to tell stories, so when L. Elisabeth Beattie remarked that her next book ought to be a Kentucky writers' cookbook, Betty Layman Receveur replied, ""Actually, all my sons ever demand of me is my pound cake."" Adding a cup of this and a pinch of that, Beattie cooked up Savory Memories, a collection of twenty-two essays about particular dishes that call up warm memories in the writers. Featuring recipes and memories from writers such as Joy Bale Boone, George Ella Lyon, Ronni Ludy, Ed McClanahan, Sena Jeter Naslund, and Richard Taylor, this is both a cookbook and a compendium of sen.